ANALISIS MODEL KURIKULUM TEKNOLOGI DALAM PENDIDIKAN ANTARA PENGEMBANGAN KOMPETENSI DIGITAL DAN KESIAPAN SISWA MENGHADAPI DUNIA KERJA MASA DEPAN - Anggun Sarastika (CV. ADIBA AISHA AMIRA, 2026)
The development of curriculum in Islamic Religious Education (PAI) has undergone significant transformation in response to the rapid advancement of digital technology. This study discusses the analysis of technology-based curriculum models in education, focusing on the development of digital competencies and students’ readiness to face the future world of work. The purpose of this study is to examine how technology integration in PAI learning can enhance digital literacy while still maintaining Islamic values as its foundation. The research method used is a qualitative approach based on literature review, relying on relevant academic books to explore theoretical concepts systematically. The findings indicate that the integration of digital technology in PAI learning improves learning effectiveness, student engagement, and competency development, although it still faces challenges such as limited infrastructure and teacher readiness. Therefore, a balanced approach between technological mastery and Islamic character education is essential in preparing students for future challenges.